2005
DOI: 10.1002/elps.200410111
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gadobenate dimeglumine by capillary zone electrophoresis coupled with electrospray‐mass spectrometry

Abstract: Highly reliable and accurate analytical methods are needed for the determination of magnetic resonance imaging (MRI) contrast agents in complex matrices of clinical interest. We demonstrate the reliability of capillary zone electrophoresis (CZE) coupled with electrospray ionization-mass spectrometry (ESI-MS) for the analysis of MultiHance (gadobenate dimeglumine), a gadolinium-based MRI agent. A sheath liquid interface connected the CE system with an electrospray mass spectrometer equipped with an ion-trap ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…New methods of examination such as magnetic resonance imaging (MRI) require the development of specific contrast agents. Campa et al [120] presented a CE-MS method for the determination of gadobenate dimeglumine (an MRI contrast agent) in various body fluids such as serum or urine. The use of an MS detector was found to be crucial as preliminary investigations revealed that UV detection was significantly biased by the matrix components of the biological samples.…”
Section: Ce-ms Of Pharmaceuticals and Related Substancesmentioning
confidence: 99%
“…New methods of examination such as magnetic resonance imaging (MRI) require the development of specific contrast agents. Campa et al [120] presented a CE-MS method for the determination of gadobenate dimeglumine (an MRI contrast agent) in various body fluids such as serum or urine. The use of an MS detector was found to be crucial as preliminary investigations revealed that UV detection was significantly biased by the matrix components of the biological samples.…”
Section: Ce-ms Of Pharmaceuticals and Related Substancesmentioning
confidence: 99%
“…Moreover, the problem of comigrating peaks was resolved with the obtainment of structural information arising from the use of a mass spectrometer detector. It has not been possible to reach the sensitivity achievable with pre-or postcolumn derivatization; however, the proposed method was successfully applied to the analysis of carbohydrates in red and white wine samples with better limits of detection with respect to those previously found with CE-UV methods [84]. A different carbohydrate profile was noticed for the two types of wine and, in general, the white one resulted richer in sugar content.…”
Section: Analysis Of Carbohydrates In Nutritionmentioning
confidence: 86%
“…Campa et al [24] investigated the analysis of gadobenate dimeglumine, a magnetic resonance imaging contrast agent, and its free ligand in water as well as in biological fluids (i.e. human serum and urine) by CZE-UV and CZE-MS.…”
Section: Determination Of Drugs and Metabolites In Biofluidsmentioning
confidence: 99%
“…Nevertheless, these sophisticated sample preparation procedures are often tedious and time-consuming. Therefore, some CE-MS applications involving sample filtration [24], protein precipitation and ultrafiltration [17] or dilution [25,26] were reported, MS being a very high selective detector. Zheng et al [17] analysed lamotrigine, an antiepileptic drug, in human plasma using CZE coupled with ESI-MS.…”
Section: Sample Preparationmentioning
confidence: 99%